PENGUNAAN MODEL PEMBELAJARAN LEARNING CYCLE 5E UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI EKOSISTEM DI KELAS V SD NEGERI KUANINO KOTA KUPANG - Korreia, Maria H; Tokan, Moses K; Koro, Maxel (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aims to improve student learning outcomes on Ecosystem materials by using the Learning Cycle 5E learning model in grade V of SD Negeri Kuanino.Based on the initial observation carried out in grade V of SD Negeri Kuanino there is a problem, namely the low learning outcomes of students in Ecosystem materials where out of 20 students who complete 2 people (10%) this is due to learning that is still centered on teachers, Lack of student involvement in learning and Lack of connection between theory and practice. In addition, most students who are less able to understand ecosystem material think that the material is boring and difficult to memorize. The problems that arise from within the students are not only caused by the students themselves, but are also supported by the teacher's inability to create learning situations that bring students interested in the material being taught The method used in this study is the class action research method (PTK). Classroom Action Research is research conducted by teachers in their own classrooms through self-reflection with the aim of improving the learning process in the classroom, so that student learning outcomes can be improved. This is in accordance with the characteristics of the classroom action research carried out to improve the learning outcomes of class V students of SD Negeri Kuanino on Ecosystem materials using the Learning Cycle 5E learning model. This research was carried out in two cycles, namely cycle I and cycle II. The instruments used were observation sheets and test questions. The number of research subjects was 20 people consisting of 8 men and 12 women. This research was carried out in grade V of SD Negeri Kuanino, Kupang City, with the results of the study showing that the results of the analysis of teacher activity in the first cycle were 64.7% and the second cycle was 83.35%. The activity of students in the first cycle is 61.87% and the second cycle is 83.12%. The learning outcomes of students in the first cycle are 45% while the second cycle is 90% where from cycle I to cycle II there has been an increase. Based on the results of this study, it can be concluded that the application of the Learning Cycle 5E learning model, when viewed from the teacher's dimension, the application of this model can broaden horizons and increase teachers' creativity in designing learning activities. Meanwhile, viewed from the student dimension, the application of this model has advantages, namely it can increase learning motivation because students are actively involved in the learning process, and help develop students' scientific attitudes and make learning more meaningful, which affects the increase in teacher activities, student activities and student learning outcomes